Peningkatan Kompetensi Lulusan Akuntansi SMK Negeri 1 Sumenep Melalui Pelatihan Accurate Accounting Software - Faisol, Moh.; Darul Firmansyah, Imam; Dwi Yandari, Aprilya; Norsain (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
The use of accuracy in the preparation of financial statements among vocational schools, especially at SMK Negeri 1 Sumenep is still new, where previously using the MYOB application. Along with the demands from the government and the industrial world, the use of accurate is an obligation that must be fulfilled in order to improve the competence and competitiveness of graduates in the world of work. The purpose of this service is to provide training and education on the use of accurate for teachers and students of the Accounting Department of SMK Negeri 1 Sumenep in order to improve their competence in preparing financial statements. The method used is in the form of accurate accounting software training for students of SMK Negeri 1 Sumenep. This service activity consists of four activities, namely activity preparation, coordination with partners, implementation of activities, and evaluation of activities. These activities will be described in detail as follows. The results of this activity based on the results of the evaluation of student understanding can be concluded that there is a change in student understanding before and after the Accurate Accounting Software training activity, where the average level of student understanding before the training is 5.19 and after the training activity the level of student understanding after the training is 7.53. This is also in line with the evaluation of students' skills in practice using Accurate Accounting Software for the purchase and sale of goods transactions has been good, even most of them are able to complete in a fairly short time.